Sample Design - Johnstone, R; Lawrence, D; Soloff, C (My University, 2005)
The Longitudinal Study of Australian Children is Australia's first national longitudinal study of children. It is a cross sequential study comprising two age cohorts: infants and children aged four to five years olds. This paper details the sample design for the study. The sample was selected from the Medicare database; a representative clustered design (children were selected from the same 311 postcodes) was chosen as it allows measurement and analysis of community level effects, and also allows for cost effective face to face interviewing. An average of 40 children per postcode in the larger states and 20 children per postcode in the smaller states and territories are participating in the study. This paper discusses the several challenges the design created and the rationale for each design feature.
1
LSAC Technical Papers
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology